Victimisation and criminal legal significance of the behavior of the victim (Journal of actual problems of jurisprudence, 2018)
The article deals with the problems of victimization and the role of the victim in the criminal law sense. For a long time the police were oriented unilaterally to work around crime and criminals without due attention to the victims of crime. As a consequence, there is still no full accounting of the victims and, therefore, do not study their personal characteristics, occasionally held events victimological prevention and general victim figure is often considered nothing more than a source of information about criminals and crime, as a party (side) of criminal -protsessualnyh relations.Key words: victimization guilty, innocentvictimization, signs of identity of the victim, harm the Criminal Procedure Law.